ESTIMASI PRODUKSI PENAMBANGAN PADA ALAT MEKANIS MEREK KOMATSU SECARA TEORITIS - Fernando Pelipus Hehakaya; Yulius G. Pangkung (INTAN Jurnal Penelitian Tambang, 2021)
This study resulted in theoretical production calculations from the handbook of Komatsu edition 30, which were calculated as coal activities, coal transportation, overburden stripping and overburden transportation. Theoretically production capacity for mechanical equipment production activities theoretically on hydraulic excavator PC 2000-8 for coal is 1,706.25 tons/hour while for overburden is 947.92 Bcm/hour, for PC 1250SP-8 1,086.75 tons/hour while overburden is 1,086.75 tons/hour. 603.75 Bcm/hour, for PC 600 overburden production obtained is 400.00 Bcm/hour while for coal is 720.00 Ton/hour and for PC 500LC-8R coal production is 630.00 Ton/hour while for overburden 350.00 Bcm/hour. The results of the calculations obtained for the HD 785-7 dump truck mechanical device for coal is 506.55 Ton/km while for overburden it is 281.42 Bcm/km, for HD 605-7R it is 332.78 Ton/km while overburden is 184.88 Bcm/km, for HD 407-7 overburden production obtained was 127.17 Bcm/km while for coal it was 228.91 Ton/km and for HD 325-7 coal production was 221.64 Ton/km while for overburden it was 123.13 Bcm/km.